Literature Review: E-Learning Sebagai Sumber dan Media Belajar dalam Kurikulum Merdeka di Sekolah Dasar - Novibriawan, Fedik (Journal of Science and Education Research, 2023)
Advances in science and technology that continue to dynamically change require changes in various sectors of life. The world of education is involved in making changes. Various innovations continue to be created to keep up with the times. Innovation in the form of using e-learning is expected to keep up with the times that continue to grow. Technology-based learning resources and media are expected to keep up with the times. The innovations created must be balanced with the policies implemented in the field. E-learning that is implemented is expected to improve the quality of education for the better. This research uses the library research method by collecting information from various quality reference sources. Creating quality learning must be balanced with the courage to innovate. Some innovations can be done by utilizing and developing various learning devices to the maximum such as the use of computers/laptops connected to the internet, creating teaching materials using various applications, and providing opportunities for students to access website services from the government.